MYDAMAI HOME apps for post COVID 19 pandemic: an innovative system to enhance well-being via work-life balance among women - Hassan, Siti Aishah; Basri, Mohammad Asraffuddien; Raja Yuosof, Raja Jamilah; Tenku Shariman, Tenku Putri Norishah; Jamaluddin, Rahimah; Zainudin, Zaida Nor; Ismail, Ismi Arif (Innovare Academics Sciences, 2020)
Following the COVID 19 pandemic outbreak, mental health and wellbeing of employed women are at stake. The Movement Control Order (MCO) has forced the majority employed women to play multiple roles in a 24/7 situation with little break if ever for her own self-care. Therefore, we propose a new employment scheme called DAMAI (Domestic Assistant Malaysian Affectionate Initiative) along with mobile and web applications online housekeepers and caregivers to improve the well-being of working women by including computer implemented genogram as mental health screening. To provide a comprehensive solution to the problem, human ecological theory, family systems theory and women well-being model are discussed. While the theory of planned behavior (TBP) and technology acceptance models are referred to in the development of web and mobile applications called MyDAMAI HOME. Finally, the presentation of the Mock Up MyDAMAI Home mark the end this paper with conclusion.